Multidisciplinary approach for hepatocellular carcinoma patients: current evidence and future perspectives - Oh, Joo Hyun; Sinn, Dong Hyun (Journal of liver cancer, 2024)
Management of hepatocellular carcinoma (HCC) is challenging due to the complex relationship between underlying liver disease, tumor burden, and liver function. HCC is also notorious for its high recurrence rate even after curative treatment for early-stage tumor. Liver transplantation can substantially alter patient prognosis, but donor availability varies by each patient which further complicates treatment decision. Recent advancements in HCC treatments have introduced numerous potentially efficacious treatment modalities. However, high level evidence comparing the risks and benefits of these options is limited. In this complex situation, multidisciplinary approach or multidisciplinary team care has been suggested as a valuable strategy to help cope with escalating complexity in HCC management. Multidisciplinary approach involves collaboration among medical and health care professionals from various academic disciplines to provide comprehensive care. Although evidence suggests that multidisciplinary care can enhance outcomes of HCC patients, robust data from randomized controlled trials are currently lacking. Moreover, the implementation of a multidisciplinary approach necessitates increased medical resources compared to conventional cancer care. This review summarizes the current evidence on the role of multidisciplinary approach in HCC management and explores potential future directions.